2015
DOI: 10.1155/2015/794256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intrastromal Riboflavin Concentration in Human Corneas after Three Corneal Cross-Linking Imbibition Procedures: A Pilot Study

Abstract: Purpose. To compare stromal riboflavin concentration after three corneal cross-linking (CXL) imbibition procedures: standard (EpiOff), transepithelial corneal (EpiOn), and iontophoresis-assisted technique (Ionto) using 0.1% hypotonic riboflavin phosphate. Methods. Randomized open-label pilot clinical study. Twelve corneas/12 patients with advanced keratoconus were randomly divided into 4 groups for CXL (n = 3). The corneas underwent imbibition with standard riboflavin EpiOff and with enhanced riboflavin soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Early clinical data on I-CXL have shown an increased permeation of the riboflavin into the stroma compared to previously mentioned trans-epithelial techniques. 32 Clinical data reported in literature showed the efficacy of I-CXL in stabilizing KC in the short term follow-up. [40][41][42] The 24-months follow-up evaluation concluded that I-CXL halted progression of keratoconus better than the pharmacological TE-CXL but less efficiently than the standard Epi-Off CXL.…”
Section: Bmentioning
confidence: 97%
See 1 more Smart Citation
“…Early clinical data on I-CXL have shown an increased permeation of the riboflavin into the stroma compared to previously mentioned trans-epithelial techniques. 32 Clinical data reported in literature showed the efficacy of I-CXL in stabilizing KC in the short term follow-up. [40][41][42] The 24-months follow-up evaluation concluded that I-CXL halted progression of keratoconus better than the pharmacological TE-CXL but less efficiently than the standard Epi-Off CXL.…”
Section: Bmentioning
confidence: 97%
“…The penetration of the (hydrophobic) corneal epithelium by riboflavin (a high molecular-weight hydrophilic substance) 25 was "facilitated" by different compounds that alter the epithelial barrier integrity: preservatives (benzalkonium chloride), surfactants and amino-alcohols such as trometamol (TRIS) and anaesthetics like tetracaine. 30,31 Nevertheless, the presence of epithelium in situ represents a physical barrier for both Riboflavin and UV-A 25,26 inducing a partial penetration, that for riboflavin results in vivo at 1/4 of the standard riboflavin concentration achieved after passive diffusion in Epi-Off S-CXL 32 and for the UV-A a 30% photo-absorption according to photobiology measurements using the standard 370 nm wavelength. 33 Moreover, an additional main limitation of the presence of epithelium in situ is oxygen consumption, estimated to be at least of 40% of the total corneal oxygen consumption, 34,35 limiting its diffusion and concentration, thus reducing the biomechanical efficacy of CXL.…”
Section: Figure 2 Comparative View Of the Lacunar Edema And Keratocymentioning
confidence: 99%
“…It is known that an adequate concentration of riboflavin in corneal stroma is imperative to obtain a biomechanical effect of corneal CXL [ 29 , 30 ]. Some authors demonstrated that in vitro stromal concentration of riboflavin increased with exposure only if the epithelium was removed, which was ascribed to the impermeability of the corneal epithelium for substances with a molecular weight greater than 100 Dalton (Da) (riboflavin has a molecular weight of 338 Da) [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, an interesting study compared stromal riboflavin concentration after three corneal cross-linking (CXL) imbibition procedures: standard (Epi-off), transepithelial corneal (Epi-on), and iontophoresis-assisted technique (Ionto), using 0.1% hypotonic riboflavin phosphate in human corneas excised during deep anterior lamellar keratoplasty. The authors found that both transepithelial CXL techniques in combination with hypotonic-enhanced riboflavin formulation (RICROLIN+) were inferior to the standard CXL technique with riboflavin passive diffusion after epithelial removal [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that, an intact corneal epithelium represents a hindrance for riboflavin solutions, which are not capable to adequately penetrate the tight junctions and uniformly diffuse into the corneal stroma [5]. Indeed, being riboflavin a large hydrophilic molecule, with an approximate weight of 340 Da, its transportation through a lipophilic epithelium, relatively low permissive for molecules >80 Da, was an indubitable issue to overcome [5,9,13,14].…”
Section: Introductionmentioning
confidence: 99%